2013
DOI: 10.1111/cid.12066
|View full text |Cite
|
Sign up to set email alerts
|

Complication and Failure Rates with Implant‐Supported Fixed Dental Prostheses and Single Crowns: A 10‐Year Retrospective Study

Abstract: After a mean exposure time of 10.75 years, high survival rates for reconstructions supported by Sand-blasted Large-grit Acid-etched implants can be expected. Ceramic chipping was the most frequent complication and was increased in dentitions with attrition and in FDPs compared with SCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
141
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 16 publications
12
141
3
8
Order By: Relevance
“…Despite the high survival rates and predictability of rehabilitating patients with single-tooth restorations using dental implants, prosthetic complications (abutment screw loosening/fracture, chipping/fracture of veneering materials, need for recementation) still remain an issue; managing these complications can cause extra amount of chair-side time, additional costs and patient dissatisfaction [2,[5][6][7][8][9][10]. Abutment screw loosening was described already in 1996 as the most common complication affecting abutments tightened with a titanium screw [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the high survival rates and predictability of rehabilitating patients with single-tooth restorations using dental implants, prosthetic complications (abutment screw loosening/fracture, chipping/fracture of veneering materials, need for recementation) still remain an issue; managing these complications can cause extra amount of chair-side time, additional costs and patient dissatisfaction [2,[5][6][7][8][9][10]. Abutment screw loosening was described already in 1996 as the most common complication affecting abutments tightened with a titanium screw [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the progresses produced by these improvements in the shortterm, recent long-term clinical studies have reported an increasing prosthetic complication occurrence with time, confirming that abutment screw loosening continues to be an important issue for clinicians [2,7,8,10]. In a long-term retrospective study evaluating the survival rates and the frequency of complications associated with implant-supported SCs [2], excellent implant survival rates were found, with a high frequency of complications (29.6%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of dental implants as intraosseous supports for different designs of prosthetic constructions demonstrates high rates of success both in 5 and in 10 years prospective [1][2][3][4]. Such method of treating the patients with symptoms of partial and full adentia, according to previous studies, usually exceeds 90% level of success [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%